Vulnerability to the HIV infection among high risk exposed women – disadvantaged girls and female prisoners in São Paulo,Brazil: contributions of nursing - Strazza, Leila; Azevedo, Raimundo S.; Boccia, Tânia M.Q.R.; Carvalho, Heráclito B. (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: aids epidemic in Brazil shows an increase of women cases. So called “aids femininely”. Understanding this vulnerability it was chosena female population with a high HIV risk infection, this is, institutionalized and prisoners. Objective: to evaluate their infection vulnerability.Methods: It was compared four different studies focus on sexual and drugs use behavior. Results: the prevalence was 2.6(Ferreira, 1997); .10(Strazza, 1999); .14 (Lopes, 1999), and .14 (Strazza, 2003). Sexual contact, with HIV positive drug partner, is the submission attitude during sexualrelationship, has to be modified as a control strategy. Conclusion: to take aim at this specific point, it is suggested to effort safe sex workshopsamong them (women and theirs partners).